THE IMPLEMENTATION OF STORYTELLING TO IMPROVE STUDENTS’ VOCABULARY MASTERY IN ENGLISH LOVERS’ COMMUNITY AT SMP NEGERI 8 MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research focused on the implementation of storytelling to improve students’ vocabulary mastery in English Lovers Community. The purpose of this research was to find out the implementation of storytelling and the obstacles of the implementation of storytelling in improving students' vocabulary mastery. This research used a qualitative research method with a descriptive approach which aimed to provide an objective description. Data collection techniques which used were observation, interviews, and documentation, in order to obtain factual and more accurate data. The results of this research indicated that the implementation of storytelling in the English Lovers Community was divided into 3 namely, preliminary activities, core activities, and closing activities. As for the obstacles experienced by teachers and students, such as limited teaching hours, students did not feel confident, students' pronunciation of vocabulary that was still wrong, students had difficulty memorizing, students felt nervous, there was a new vocabulary, parts of storytelling such as voice intonation, deepening of character, and expression. However, these obstacles could be overcome by maximizing time and motivating students and continuing to practice so that students' vocabulary mastery increases.